2021
DOI: 10.1002/cne.25230
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of astrocytes in vocal production circuits of common marmoset (Callithrix jacchus)

Abstract: Astrocytes, the star-shaped glial cells, are the most abundant non-neuronal cell population in the central nervous system. They play a key role in modulating activities of neural networks, including those involved in complex motor behaviors. Common marmosets (Callithrix jacchus), the most vocal non-human primate (NHP), have been usedto study the physiology of vocalization and social vocal production. However, the neural circuitry involved in vocal production is not fully understood. In addition, even less is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 112 publications
(121 reference statements)
1
14
0
Order By: Relevance
“…Additionally, this antibody stains a double band at 245-395kDA on Western Blot Analysis (Key et al 1993). We have recently showed that this antibody also reacts with marmoset’s astrocytes (Turk and SheikhBahaei 2021).…”
Section: Methodsmentioning
confidence: 96%
See 4 more Smart Citations
“…Additionally, this antibody stains a double band at 245-395kDA on Western Blot Analysis (Key et al 1993). We have recently showed that this antibody also reacts with marmoset’s astrocytes (Turk and SheikhBahaei 2021).…”
Section: Methodsmentioning
confidence: 96%
“…This GFAP antibody was raised against purified glial filament protein (Debus, Weber, & Osborn, 1983). We have previously shown the specificity of this antibody to detect astrocytes in marmoset tissue as well (Turk and SheikhBahaei 2021).…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations